The Role of the College of Islamic Sciences University of Sulaymaniyah in Preserving Religious Diversity: A Descriptive Analytical Study - Ahmed, ass prof: Mahdi Qader Ahmed (Sulaimani Journal for Humanities, 2026)
Preserving religious diversity is a divine command, a human objective, and a scientific process. The College of Islamic Sciences at the University of Sulaimani embraces this responsibility toward both humanity and the Creator in the esteemed land of the Kurdistan Region of Iraq. Given the significance of this matter and the responsibility it entails, I have chosen to examine the role of the college in maintaining religious diversity. This research aims to shed light on the college’s role in promoting a culture of coexistence and acceptance of religious diversity in the Kurdistan Region through a descriptive-analytical methodology. The study is structured into three main sections. The first section defines the concept of religious diversity and explores the role of educational institutions in fostering it. The second section analyzes the academic curricula at the College of Islamic Sciences, assessing their coverage of religious pluralism and tolerance, evaluating their effectiveness, and providing recommendations for their improvement to enhance the understanding of interfaith coexistence. The final section highlights key contributors to religious diversity through academic activities such as conferences, seminars, scholarly meetings, publishing research in peer-reviewed journals, and organizing training programs for students. These efforts play a fundamental role in reinforcing the principles of diversity and pluralism, making them worthy of continuous effort and attention. This study describes, analyzes, evaluates, and proposes measures for fostering a diverse, tolerant, and progressive society. Achieving this goal is a collective endeavor that requires the cooperation of governmental, educational, religious, legal, and media institutions
Keywords: College of Islamic Sciences; religious diversity; peace; curriculum